Neurobiology of the relationship between sleep disorders and headaches: an integrative review - Ferreira, Pablo Guarisco; Pereira, Kleber Fernando; Ricardi, Lara Henriqueta Bussolaro; Neto, Marcelo Alvarenga de Carvalho; Pagliarin, Luis Gustavo; Souza, Cristiano de Bem Torquato de; César, Alcântara Ramos de Assis (Headache Medicine, 2023)
Full abstract in PDF.